Economic Diversification in Iraq: Overcoming Oil Dependency and Building a Sustainable Future - Ali, Zhino; Hussein, Sima (Business and Investment Review, 2024)
Iraq’s economy is heavily dependent on its oil sector, which accounts for over 90% of government revenues, leaving the country vulnerable to fluctuations in global oil prices and geopolitical instability. This paper explores the prospects and challenges of economic diversification in Iraq, focusing on potential growth sectors such as agriculture, manufacturing, technology, and tourism. Despite the country's rich natural resources and strategic opportunities, Iraq faces significant barriers, including political instability, inadequate infrastructure, and a lack of skilled labor. By analyzing international best practices and conducting expert interviews, the paper highlights key strategies for fostering a more diversified and resilient economy. The findings suggest that a comprehensive approach involving government reforms, investment in infrastructure, and educational improvements is crucial for Iraq's successful transition to a diversified economy. The paper concludes with policy recommendations aimed at reducing Iraq's dependence on oil and creating a more sustainable economic future.